Correlation of Laboratory Profile and Clinical Features in Dengue Viral Illness in the Pediatric Population: A Retrospective Analysis - Keyur D Mahajan; Rajan Joshi (Pediatric Infectious Disease)
Objective: To study the correlation between laboratory profile and clinical features in dengue viral illness in the pediatric population. Materials and methods: A retrospective study was conducted on pediatric patients, ranging from 0 to 16 years old, diagnosed with dengue viral illness and admitted to the pediatric care unit between January and December of 2022. The outcome of interest measured was the correlation between laboratory profile and clinical features of dengue patients. Depending on data distribution, appropriate tests were applied for analysis. Data were collected from hospital software records according to the set pro forma. The medical notes and the Laboratory Information System were evaluated using a tool for standard assessment. Conclusion: The presentation of dengue viral illness can vary, and it is crucial to diagnose it early for effective patient management. Upon admission, common clinical presentations include fever, nausea, vomiting, abdominal pain, body ache, leg pains, and retro-orbital pain. However, there was no association between presenting complaints and progression to severe illness. Although all five patients who died from the disease were females, it is inconclusive if sex is a significant risk factor for severe disease. Likewise, the patient's age has no association with the progression to severe disease. Platelet count, serum (Sr) albumin, Sr glutamic-oxaloacetic transaminase (SGOT)/Sr glutamic pyruvic transaminase (SGPT), prothrombin time (PT) international normalized ratio (INR), and Sr ferritin levels are all excellent predictors of prognosis for severe dengue. Peak Sr ferritin levels indicating the highest immune response were seen on day 5 of illness and were not affected by the age or sex of the patient.